Peran Orang Tua Dalam Melatih Pembiasaan Anak Terhadap Toilet Training - Sari, Eka Angela; Haryono, Mimpira; Asnawati, Asnawati (Early Childhood Research and Practice, 2024)
The purpose of this study was to determine the role of parents in training children's habituation to toilet training at PAUD Aisyah. The type of research used in this study is descriptive qualitative research. The data collection methods used are interviews, observation and documentation. The data sources are parents at PAUD Aisyah Pondok Kelapa and documentation in the form of photographs during interviews with parents of children during learning at PAUD Aisyah. The data analysis techniques used are data reduction recording the results of interviews with parents of children, recording coding the data according to the information provided by informants, displaying data describing the results of interviews with parents of children, and data verification rethinking the results of interviews, reviewing field notes, rethinking observation data and field findings, in order to draw conclusions from the results of the research that has been done. The results of this study describe the role of parents in training children's habituation to toilet training at PAUD Aisyah Pondok Kelapa, Central Bengkulu Regency.